Given two intersecting lines, let L 2 be the line with the larger angle of inclination ϕ 2 , and let L 1 be the line with the smaller angle of inclination ϕ 1 . We define the angle θ between L 1 and L 2 by θ = ϕ 2 − ϕ 1 . (See the accompanying figure.) (a) Prove: If L 1 and L 2 are not perpendicular, then tan θ = m 2 − m 1 1 + m 1 m 2 where L 1 and L 2 have slopes m 1 and m 2 . (b) Prove Theorem 10.4.5. [Hint: Introduce coordinates so that the equation x 2 / a 2 + y 2 / b 2 = 1 describes the ellipse, and use part (a).] (c) Prove Theorem 10.4.6. [Hint: Introduce coordinates so that the equation x 2 / a 2 − y 2 / b 2 = 1 describes the hyperbola, and use part (a).]
Given two intersecting lines, let L 2 be the line with the larger angle of inclination ϕ 2 , and let L 1 be the line with the smaller angle of inclination ϕ 1 . We define the angle θ between L 1 and L 2 by θ = ϕ 2 − ϕ 1 . (See the accompanying figure.) (a) Prove: If L 1 and L 2 are not perpendicular, then tan θ = m 2 − m 1 1 + m 1 m 2 where L 1 and L 2 have slopes m 1 and m 2 . (b) Prove Theorem 10.4.5. [Hint: Introduce coordinates so that the equation x 2 / a 2 + y 2 / b 2 = 1 describes the ellipse, and use part (a).] (c) Prove Theorem 10.4.6. [Hint: Introduce coordinates so that the equation x 2 / a 2 − y 2 / b 2 = 1 describes the hyperbola, and use part (a).]
Given two intersecting lines, let
L
2
be the line with the larger angle of inclination
ϕ
2
,
and let
L
1
be the line with the smaller angle of inclination
ϕ
1
.
We define the angle
θ
between
L
1
and
L
2
by
θ
=
ϕ
2
−
ϕ
1
.
(See the accompanying figure.)
(a) Prove: If
L
1
and
L
2
are not perpendicular, then
tan
θ
=
m
2
−
m
1
1
+
m
1
m
2
where
L
1
and
L
2
have slopes
m
1
and
m
2
.
(b) Prove Theorem 10.4.5. [Hint: Introduce coordinates so that the equation
x
2
/
a
2
+
y
2
/
b
2
=
1
describes the ellipse, and use part (a).]
(c) Prove Theorem 10.4.6. [Hint: Introduce coordinates so that the equation
x
2
/
a
2
−
y
2
/
b
2
=
1
describes the hyperbola, and use part (a).]
For each given function f(x) find f'(x) using the rules learned in section 9.5.
1. f(x)=x32
32x
2. f(x)=7x+13
3. f(x) =
x4
4. f(x) = √√x³
5. f(x) = 3x²+
3
x2
Find:
lim x →-6 f (x)
limx-4 f (x)
lim x-1 f (x)
lim x →4 f (x)
(-6,3) •
(-1,5)
-8
-7
(-6,-2)
4+
(4,5)
(4,2) •
(-1,1)
-6
Need a deep-dive on the concept behind this application? Look no further. Learn more about this topic, calculus and related others by exploring similar questions and additional content below.